Bioprinting: Aqueous Two‐Phase Emulsion Bioink‐Enabled 3D Bioprinting of Porous Hydrogels (Adv. Mater. 50/2018) - Ying, Guo‐Liang; Jiang, Nan; Maharjan, Sushila; Yin, Yi‐Xia; Chai, Rong‐Rong; Cao, Xia; Yang, Jing‐Zhou; Miri, Amir K.; Hassan, Shabir; Zhang, Yu Shrike (Advanced materials (Weinheim), 2018)
A cell‐benign approach to directly bioprint porous‐structured hydrogel constructs is developed by Yu Shrike Zhang and co‐workers in article number 1805460, taking advantage of an aqueous two‐phase emulsion bioink. The bioink contains two immiscible aqueous phases of a cell/gelatin methacryloyl (GelMA) mixture and poly(ethylene oxide) (PEO) can be photocrosslinked from the GelMA phase to fabricate a predesigned cell‐laden hydrogel construct, while the pores are formed by subsequently removing the PEO phase.